The Definitive Guide to CentOS - Membrey, Peter; Verhoeven, Tim.; Angenendt, Ralph; SpringerLink (Online service) (Berkeley, CA : Apress, 2009)
CentOS is just like Red Hat, but without the price tag and with the virtuous license. When belts have to be tightened, we want to read about an OS with all the features of a commercial Linux variety, but without the pain. The Definitive Guide to CentOS is the first definitive reference for CentOS and focuses on CentOS alone, the workhorse Linux distribution, that does the heavy lifting in small and medium-size enterprises without drawing too much attention to itself. Provides tutorial and hands-on learning but is also designed to be used as a reference Bases all examples on real-world tasks that readers are likely to perform Serves up hard-won examples and hints and tips from the author's experiences of CentOS in production.
Getting Started with CentOS -- Introducing CentOS -- Installing CentOS -- Getting Started with CentOS -- Using Yum -- Going into Production -- Using Apache -- Setting Up Mail -- Understanding DNS -- Setting Up DHCP -- Sharing Files with Samba -- Setting Up Virtual Private Networks -- Enterprise Features -- Using Core Builds -- Using High Availability -- Monitoring Your Network Using Nagios.
Keywords: Computer science; Computer Science; Computer Science, general; Electronic books